Students' Metacognitive Ability Mathematical Problem-Solving through the Problem-based Learning Model - Zia Anjelina; Usman Usman; Marwan Ramli (Didaktik Matematika, 2021)
Students lack metacognitive ability despite its vital role in mathematical problem-solving. The problem-based Learning (PBL) model is one of the learning models to improve metacognitive ability in problem-solving. This study aimed to analyze the students'metacognitive ability in mathematical problem solving through PBL and examine its improvement. This present study applied the explanatory sequential mixed-method design. The population was the Year 11 students from one of the senior high schools in South Aceh Regency, Indonesia. Data collection was conducted using three instruments: pre-test, post-test, and interview guidelines. The pre-test and post-test data were analyzed using the t-test, while students' metacognitive ability was analyzed qualitatively. The results showed that students' metacognitive ability in mathematical problem solving through the PBL model was increased. Furthermore, students' metacognitive abilitywas at the semi-reflective use, the strategic use, the aware use levels for high-ability, medium-ability, and low-ability groups.